The Role of The People Representative Council of Pematang Siantar City, Indonesia, in Supporting Community Welfare - Sabriani Royana Simanjuntak; Haposan Siallagan (Golden Ratio of Data in Summary, 2026)
This study examines the role of the Regional People's Representative Council (Dewan Perwakilan Rakyat Daerah/DPRD) of Pematang Siantar City in supporting community welfare within the framework of regional autonomy as mandated by Law Number 23 of 2014 concerning Regional Government. As a local representative institution, the DPRD plays a strategic role in shaping welfare-oriented public policies through its legislative, budgetary, and oversight functions. However, empirical studies that explicitly analyze the contribution of these functions to community welfare at the city level remain limited. The findings show that the DPRD of Pematang Siantar City primarily performs its legislative function by discussing and approving draft regional regulations proposed by the executive. In contrast, regulations initiated by the DPRD remain limited. In the budgetary function, the DPRD plays a crucial role in approving the Regional Revenue and Expenditure Budget (APBD) and directing allocations toward welfare-related sectors. However, improvements are needed in terms of transparency and timeliness in budget deliberations. Meanwhile, the oversight function is carried out through working meetings, field visits, and recess activities; however, the absence of systematic follow-up mechanisms limits its effectiveness in ensuring the implementation of welfare-oriented policies. This study concludes that while the DPRD of Pematang Siantar City has fulfilled its formal institutional functions, its contribution to community welfare has not yet reached an optimal level. Strengthening the capacity of DPRD members, enhancing transparency in legislative and budgetary processes, and increasing community participation are essential to improving the effectiveness of the DPRD in supporting sustainable community welfare. The findings of this study make significant empirical contributions to the literature on regional governance and provide policy-relevant insights for strengthening the role of local legislative institutions in Indonesia.